Levels of Total Antioxidant Capacity (TAC) and oxidative stress in type 2 diabetes mellitus in Kanpur region - Muriki Naresh Kumar; Pallavi Anand; Anil Kumar (Al Ameen Medical College, 2020)
Background: Hyperglycemia is associated with decreased antioxidant capacity and increased oxidative stress. Micro and Macro vascular complications are mainly caused by oxidative stress in Diabetes Mellitus. The total antioxidant capacity assay is used to determine total antioxidant power of plasma. Objective: To find levels of Total anti oxidant capacity, oxidative stress and Lipid profile in Type 2 Diabetic patients. Methods: We assessed Total Antioxidant Capacity (TAC), Malondialdehyde (MDA) and Lipid Profile in 120 patients of type 2 diabetes Mellitus and 120 healthy controls. This study was conducted in Rama Medical College, Hospital & Research centre, Kanpur. Student t test was used for statistical analysis. Result: The study showed that decreased total antioxidant capacity, increased Malondialdehyde levels and altered Lipid profile in type 2 diabetics compared with healthy controls. Conclusion: Total Antioxidant Capacity (TAC) significantly decreased in Type 2 DM compared to control group.